Upaya Peningkatan Motivasi dan Kemampuan Membaca Permulaan Melalui Media Kartu Huruf Pada Siswa Kelas 1 SD Negeri 1 Pakis Kecamatan Kradenan Tahun Pelajaran 2017/2018 - Sunarti, Sri (Efektor, 2018)
The main problem in this research is the low ability of reading the beginning of first grade students of SD Negeri 1 Pakis in Indonesian Language subjects. One of the factors that causes low reading ability is the learning process still using conventional media that is by using whiteboard and learning is only centered on the teacher and make passive students. The objectives of this research are to find out whether the letter card media can improve the motivation and readiness of reading in the first grade of SD Negeri 1 Pakis, Kradenan Sub-district, Grobogan District. The variables that were subjected to changes in this classroom action research were to improve the motivation and ability to read the beginning of the first grade students, while the action variables used in this study were the letter card media. Action Research This class is carried out with two cycles of 25 students, each cycle consisting of action planning, observation and reflection. From the results of the first cycle action obtained learning outcomes read the beginning of students with a grade average of 69 with the percentage of students 52%. The result of second cycle action is obtained by learning result of reading the beginning of student with the average value 78,67 with the percentage of student 92%. Thus, it can be concluded that the learning of Bahasa Indonesia (reading the beginning) with the use of letter card media can increase the reading ability of the beginning in class I SD Negeri Pakis of Kradenan Sub-district Grobogan Regency.